Portable electronic bronchoscopy for clinical application: a multi-institutional randomized instrument validation study. Issue 6 (June 2022) - Qiu, Yuanhua; Feng, Ganzhu; Yu, Zhen; Wang, Limin; Chen, Enguo
Objective: Electronic bronchoscopy is routinely used for the diagnosis and treatment of lung and bronchial disorders. However, the devices used are normally large and costly. Here, we evaluated the clinical effectiveness of a portable electronic bronchoscope produced by Zhejiang UE Medical Corp., the UE-EB. Methods: We conducted a multi-institutional, randomized, single-blind, non-inferiority and parallel-group controlled clinical trial. Participants were randomly assigned 1:1 to the experimental group or control group. The primary indicator was the effectiveness of the device. Safety indicators were assessed from enrollment to 3 days after the operation. Results: The UE-EB had good consistency between groups during the procedure, and the effective rate was 100.00% in both groups. The difference value (95% confidence interval) between the two groups was 0.00% (−5.45%, 5.45%), and the lower limit was greater than −10% (negative non-inferiority margin). There was also no difference between the two groups in terms safety indicators. Conclusions: The portable electronic bronchoscope described in this study showed reliable effectiveness and safety. This device is worth promoting and applying in clinical practice. Research registry number: ZXLB20200295 (Zhejiang Medical Products Administration, China).